2020
DOI: 10.1177/1069031x20961112
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate Consumers’ Adaptations and Food Brand Choices: A Compensatory Control Perspective

Abstract: The number of expatriates has been steadily growing during the last two decades. For these reasons, academia has exhibited a growing research interest in expatriates’ food consumption choices. Although interest is there, the extant literature is inconclusive about conditions under which expatriate consumers make trade-offs between host-country (local) and global food products and brands. The present study presents mechanisms that explain expatriate consumers’ compensatory coping behaviors and choices between l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 77 publications
(149 reference statements)
1
23
0
Order By: Relevance
“…Hence, our study enriches the literature on expatriate adaptation efforts by showing that besides social identification effects (Bardhi et al, 2012;Miocevic and Zdravkovic, 2020a;Miocevic and Zdravkovic, 2020b), the differentiation effects should not be ignored (Berger and Heath, 2007;Brewer, 1991;Miocevic and Mikulic, 2021). From the standpoint of practitioners, our study illuminates a novel perspective by suggesting that expatriates are not a homogenous market segment, and therefore, their adaptation efforts occurring in public and private domains might vary significantly.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…Hence, our study enriches the literature on expatriate adaptation efforts by showing that besides social identification effects (Bardhi et al, 2012;Miocevic and Zdravkovic, 2020a;Miocevic and Zdravkovic, 2020b), the differentiation effects should not be ignored (Berger and Heath, 2007;Brewer, 1991;Miocevic and Mikulic, 2021). From the standpoint of practitioners, our study illuminates a novel perspective by suggesting that expatriates are not a homogenous market segment, and therefore, their adaptation efforts occurring in public and private domains might vary significantly.…”
Section: Introductionsupporting
confidence: 70%
“…The research on acculturation traits of expatriate consumers has been relatively scarce and influenced mainly by the consumer culture theory (Bardhi et al, 2012;Bengtsson et al, 2010;Figueiredo and Uncles, 2015;Gilly, 1995;Thompson and Tambyah, 1999). Some recent studies tap into the impact of acculturation behaviors on food adaptation of expatriates (Bundy, 2017;Miocevic and Zdravkovic, 2020a;Miocevic and Zdravkovic, 2020b;Miocevic et al, 2021b).…”
Section: Acculturation Through Social Interactions With the Local Com...mentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned studies revealed that growing interest observed among individuals regarding intake of processed and high calorie packaged food (Miocevic & Zdravkovic, 2020). Therefore, scholars and practitioners suggested to develop sense of healthy packaged food intention among individuals (Baker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%